Combined administration of lauric acid and glucose improved cancer‐derived cardiac atrophy in a mouse cachexia model. Issue 12 (2nd October 2020) - Nukaga, Shota; Mori, Takuya; Miyagawa, Yoshihiro; Fujiwara‐Tani, Rina; Sasaki, Takamitsu; Fujii, Kiyomu; Mori, Shiori; Goto, Kei; Kishi, Shingo; Nakashima, Chie; Ohmori, Hitoshi; Kawahara, Isao; et al.
Abstract: Cancer‐derived myocardial damage is an important cause of death in cancer patients. However, the development of dietary interventions for treating such damage has not been advanced. Here, we investigated the effect of dietary intervention with lauric acid (LAA) and glucose, which was effective against skeletal muscle sarcopenia in a mouse cachexia model, on myocardial damage. Treatment of H9c2 rat cardiomyoblasts with lauric acid promoted mitochondrial respiration and increased ATP production by Seahorse flux analysis, but did not increase oxidative stress. Glycolysis was also promoted by LAA. In contrast, mitochondrial respiration and ATP production were suppressed, and oxidative stress was increased in an in vitro cachexia model in which cardiomyoblasts were treated with mouse cachexia ascites. Ascites‐treated H9c2 cells with concurrent treatment with LAA and high glucose showed that mitochondrial respiration and glycolysis were promoted more than that of the control, and ATP was restored to the level of the control. Oxidative stress was also reduced by the combined treatment. In the mouse cachexia model, myocardiac atrophy and decreased levels of a marker of muscle maturity, SDS‐soluble MYL1, were observed. When LAA in CE‐2 diet was orally administered alone, no significant rescue was observed in the cancer‐derived myocardial disorder. In contrast, combined oral administration of LAA and glucose recovered myocardial atrophy and MYL1 to levels observed in the control without increase in the cancer weight. Therefore, it is suggested that dietary intervention using a combination of LAA and glucose for cancer cachexia might improve cancer‐derived myocardial damage. Abstract : We elucidated that cancer‐derived myocardial damage results mainly from oxidative stress. The combined administration of LAA and glucose can effectively provide protective effects against myocardial damage and promote recovery.